1986
DOI: 10.1159/000146283
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol-Induced Myocardial Ischemic Injury in the Rabbit: Functional and Ultrastructural Alterations

Abstract: The functional and ultrastructural changes observed during myocardial ischemic injury (Mil) in the rabbit are described. Mil was induced by repeated subcutaneous injections of increasing doses of isoproterenol (ISO; 0.5 mg/kg on day 1, to 15.5 mg/kg on day 15). Measurement of cardiovascular changes revealed a significant decrease in the mean arterial pressure and an increase in heart rate of the ISO-treated animals. ISO treatment also initiated a variety of atrial and ventricular arrhythmias, including ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
3

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
2
4
0
3
Order By: Relevance
“…Hypoxia has been largely involved in the pathogenesis of myocardial infarctlike pathologies either in clinical or in experimental isoproterenol-induced myocardial necrosis. Some similar findings have been observed in clinical infarcts, in experimental in vivo models and in the present results (Rona et al 1959;Ferrans et al 1969;Fleckenstein 1971;Maroko & Braunwald 1976;Jennings & Reimer 1981;Todd et al 1985a & b;Rona 1985;Bhimji et al 1986;Nayler 1988). These similarities validate our present model from an anatomical point of view.…”
Section: Discussionsupporting
confidence: 90%
“…Hypoxia has been largely involved in the pathogenesis of myocardial infarctlike pathologies either in clinical or in experimental isoproterenol-induced myocardial necrosis. Some similar findings have been observed in clinical infarcts, in experimental in vivo models and in the present results (Rona et al 1959;Ferrans et al 1969;Fleckenstein 1971;Maroko & Braunwald 1976;Jennings & Reimer 1981;Todd et al 1985a & b;Rona 1985;Bhimji et al 1986;Nayler 1988). These similarities validate our present model from an anatomical point of view.…”
Section: Discussionsupporting
confidence: 90%
“…Cristae fragmentation and matrix swelling have been reported through a variety of perturbations [43], [44], [45], [46] including myocardial ischemia [47], [48]. The cristae fragmentation observed in our longitudinal sections produced an interesting honeycomb-like pattern in cross-section that was not observed in NC mitochondria (Figure 3).…”
Section: Discussionmentioning
confidence: 58%
“…These micrographs revealed that the mitochondrial structures in LOF and HOF changed significantly comparing with control; differences were primarily observed in the cristae, but different types and extents of morphological changes were observed. The LOF mitochondria were representative of the two major abnormal classes: the first class is the honeycomb-patterned mitochondria (volume fraction 23.1±5.7%, Figure 1C) as reported before [28], and the second class is with large amplitude swelling (as indicated by the transparent “empty” spaces) (volume fraction 6.8±1.8%, Figure 1D), which can be found in myocardial ischemia in mammals [29], [30]. However, these two structural aberrations were not observed in the HOF.…”
Section: Resultsmentioning
confidence: 64%
“…In addition, 2 mitochondrial structural disturbances that were similar to, albeit much less severe than, the changes observed under pathological conditions were observed in LOF and HOF. For example, large-amplitude swelling, which can occur due to myocardial ischemia in mammals [29], [30], was observed in LOF, and mitochondria with regionally swollen and rounded cristae, which were similar to those found in flies that were treated acutely with extremely high oxygen levels, were observed in HOF [39]. Furthermore, changes in the enzymatic activities of the respiratory chain complexes were detected in the LOF and HOF samples.…”
Section: Discussionmentioning
confidence: 62%